The impact of private investments in English club football on sport performance - Pires Carvalho, Ricardo (2023)
The present thesis aims to investigate the impact of private investment on the sporting performance of English football clubs. In the recent past, the English Premier League (EPL) and the Championship have attracted a significant number of domestic and foreign investors, which have led to an increased level of competition and entertainment, as well as, to a boost in the financial resources that are available for these clubs. Despite this new trend around the European football industry, most of the clubs competing in the top-tiers of the European leagues have experienced difficulties in obtaining reasonable financial results, with low degree of profitability and growing levels of debt. Considering that the football industry combines two relevant indicators of success, namely the financial and the sporting performance (Wilson, Plumley and Ramchandani, 2013), this investigation links these two performance dimensions with the entrance of foreign investors in the English football business. In agreement with the previous studies, this research is conducted using an econometric model to test the relationship between the above-mentioned topics. By setting an unbalanced panel data of the English Premier League and the Championship clubs from the 2011/2012 to 2020/2021 seasons, this paper tries to interpret the relationship between the number of national league points per game and the presence of foreign investment in English clubs. The findings of this investigation provide insights into the effectiveness of foreign investment in the English football and contribute to the ongoing research and discussions around this business framework.